Impact of target vessel choice on outcomes following percutaneous coronary intervention in patients with a prior coronary artery bypass graft. Issue 6 (3rd September 2021) - Beerkens, Frans J.; Singh, Ranbir; Cao, Davide; Claessen, Bimmer E.; Nicolas, Johny; Sartori, Samantha; Snyder, Clayton; Camaj, Anton; Giustino, Gennaro; Power, David; Razuk, Victor; Jones, Davis; et al.
Abstract: Objectives: To evaluate and compare characteristics and clinical outcomes of percutaneous coronary intervention (PCI) among target vessel types in patients with a prior coronary artery bypass graft (CABG) surgery. Background: Patients with a prior CABG often require repeat revascularization with PCI. Graft PCI has been associated with worse outcomes compared to native vessel PCI, yet the optimal PCI strategy in prior CABG patients remains unknown. Methods: We stratified prior CABG patients who underwent PCI at a tertiary‐care center between 2009 and 2017 by target vessel type: native vessel, venous graft, and arterial graft. The primary outcome of major adverse cardiac events (MACE) was a composite of all‐cause death, myocardial infarction, stent thrombosis, or target vessel revascularization up to 1 year post‐PCI. Results: Prior CABG patients ( n  = 3983) represented 19.5% of all PCI interventions during the study period. PCI was most frequently performed on native vessels ( n  = 2928, 73.5%) followed by venous ( n  = 883, 22.2%) and arterial grafts ( n  = 172, 4.3%). Procedural success and complications were similar among the groups; however, slow‐ and no‐reflow phenomenon was more common in venous graft PCI compared to native vessel PCI (OR 4.78; 95% CI 2.56–8.95; p  < 0.001). At 1 year, there were no significant differences in MACE or in its individual components. Conclusions: Target vessel choice did not appear to affect MACE at 1 year in a large cohort of patients with prior CABG undergoing PCI. Whether PCI of surgical grafts versus native arteries truly results in similar outcomes warrants further investigation in randomized controlled trials.